Consumption of Galactooligosaccharides together with Probiotics Stimulates the In Vitro Peripheral Blood Mononuclear Cell Proliferation and IFNγ Production in Healthy Men. (30th November 2011) - Holma, Reetta; Kekkonen, Riina A.; Hatakka, Katja; Poussa, Tuija; Vaarala, Outi; Adlercreutz, Herman; Korpela, Riitta
Abstract : Probiotics and prebiotics modify the intestinal environment and could have immunomodulatory effects. The proliferation of spontaneous and phytohemagglutinin-stimulated peripheral blood mononuclear cells (PBMCs) and their production of interleukin-4, interleukin-5, transforming growth factor- β 1, and interferon- γ (IFN γ ) were determined in eighteen men at the baseline and during a 2-week period of probiotics (mixture of Lactobacillus rhamnosus GG, Lactobacillus rhamnosus LC705, Propionibacterium freudenreichii ssp. shermanii JS, and Bifidobacterium breve Bb99) and galactooligosaccharides (GOSs) (3.8 g/day). The spontaneous and stimulated proliferation of PBMC increased from the baseline during probiotics+GOS (P < 0.001 ). The secretion of IFN γ, but not other cytokines, by stimulated PBMC increased during the same period (P < 0.05 ). In conclusion, the consumption of this probiotic mixture including GOS appears to increase the capacity of PBMC to proliferate and release IFN γ selectively in healthy men.